Current strategies for targeted therapy of liver fibrosis - D. V. Garbuzenko (Бюллетень сибирской медицины, 2022)
Liver fibrosis (LF) is an unfavorable event in the natural course of chronic liver diseases (CLD), therefore, early implementation and widespread use of antifibrotic therapy methods is a pressing issue in hepatology. The aim of the review was to describe current approaches to targeted therapy of LF.PubMed database, Google Scholar search engine, Cochrane Database of Systematic Reviews, eLIBRARY.RU scientific electronic library, as well as reference lists of articles were used to search for scientific articles. The publications that corresponded to the aim of the study were selected for the period from 1998 to 2021 by the terms “liver fibrosis”, “pathogenesis”, and “treatment”. Inclusion criteria were restricted to targeted therapy of LF.Despite the growing evidence for reversibility of LF, there are currently no effective or clinically approved regimens for its specific therapy. However, taking into account the relevance of the issue, scientific research in this area is necessary. Multiple drugs with a good safety profile have been studied, which, though intended for other purposes, can have a positive effect on LF. In addition, a number of innovative approaches that differ from pharmacotherapy inspire optimism about finding a solution to this problem. It is obvious that studies focused on well-characterized groups of patients with confirmed histologic, elastography, clinical, and radiological parameters are required. This is a challenging task, since the key point will be stratification of risk based on ethnicity, etiology, and clinical status, and very large samples will be required for a reliable assessment. Nevertheless, the solution will increase efficiency of treatment for patients with CLD, improve their prognosis and quality of life, and significantly reduce the need for liver transplantation, a demand for which remains extremely high worldwide.